STUDENTS’ PERCEPTION ON THE USE OF E-LEARNING IN THE ENGLISH SUBJECT - Munalia Munalia; Kurnia Saputri; Finza Larasati; Gunawan Ismail (Universitas Mahaputra Muhammad Yamin, 2022)
The objectives of this study were to find out students’ perception about E-learning in English Subject to the Tenth Grade Students’ Madrasah Aliyah Darun Najah Bangun Jaya and to find out strengths and weaknesses in using E-learning faced by the Tenth Grade Students’ Madrasah Aliyah Darun Najah Bangun Jaya. This study used a mix method by using questionnaires and open-ended questionnaires. The researchers used total sampling and the sample was 69 students. The data were collected through an online questionnaire distributed through Google Form and WhatsApp application. For analyzing the data, the researchers used a percentage analysis formula. Based on the result of the questionnaire, 36 students or 52.2% had negative perception of E-learning in English subjects, 31 students or 44.9% had positive perception and 2 students or 2.8% had neutral perception. It could be concluded that the Tenth Grade Student of Madrasah Aliyah Darun Najah Bangun Jaya has negative perception on E-learning in English subject. The result of the open-end questionnaire found that the strength in using the WhatsApp application is that it is easier to submit the assignment. E-learning can eliminate hesitation / unconfidence to practice English, and interaction and communication between teacher and students better. The weakness in using E-learning was students are difficult to understand the material given. They faced limited internet access and the time was not flexible, so that learning activities became ineffective.